The Effectiveness of Writing Learning with the Storytelling Method Based on Local Folktales to Improve Student Literacy in Junior High School - Syamsul Anwar; Aida Azizah (Journal of Pedagogy and Education Science, 2026)
This study aims to test the effectiveness of a storytelling method based on local folklore in improving junior high school students' writing literacy skills. The background of this study stems from students' low writing skills due to limited engaging learning methods and the lack of integration of local cultural values into the learning process. This study used a quantitative approach with a quasi-experimental pretest–posttest control group design. The study subjects consisted of two groups: an experimental group taught using a storytelling method based on local folklore and a control group taught using conventional methods. Data were collected through narrative writing tests, observations of learning activities, and semi-structured interviews. The results showed a significant difference between the learning outcomes of the experimental and control groups. The mean posttest score for the intervention group reached 81.5, and the control group’s score was 72.4. The t-test results showed t-count (3.75) > t-table (2.00) at a significance level of 0.05. The greatest improvement occurred in the content and creativity aspects, followed by narrative structure, language, and mechanics. In addition to improved learning outcomes, students also demonstrated greater enthusiasm, participation, and emotional engagement during learning. These findings reinforce Vygotsky's social constructivism theory and Bruner's concept of narrative learning, which argues that the learning process becomes more meaningful when integrated with a cultural context. Overall, this study concludes that the storytelling method based on local folklore is effective not only in improving writing skills but also in fostering students' cultural awareness and character. This approach is recommended as a culture-based literacy strategy for Indonesian language learning at the junior high school level